(untitled) - Cohen, Harold (New York, NY., 2003)
Cohen's introductory complex analysis text contains some material not found in other popular texts, including singularity structure of functions defined by integrals which cannot be evaluated in terms of elementary functions, and an emphasis on practical applications such as the analysis of simple AC circuits. Cohen (physics and astronomy, California State U., Los Angeles) covers topics include using Cauchy's residue theorem to evaluate definite integrals, and using dispersion relations for determining a complete function from either the known real or imaginary component. The text serves beginning and second courses in the subject.
Keywords: Functions of complex variables,Mathematical analysis